Recognition of the Simple Groups 2D8((2n)2) - Ebrahimzadeh Behnam (Annals of the West University of Timisoara: Mathematics and Computer Science, 2019)
One of the important problems in finite groups theory is group characterization by specific property. Properties, such as element orders, set of elements with the same order, the largest element order, etc. In this paper, we prove that the simple groups 2D8((2n)2)where, 28n+ 1 is a prime number are uniquely determined by its order and the largest elements order.